Textual and Visual Correspondence Between the Novel and the Film: The Epistolary Narrative of Love, Simon - Özgür Çalışkan (Selçuk İletişim)
Love, Simon (2018) is an American comedy-drama film directed by Greg Berlanti and based on Becky Albertalli's novel Simon vs. the Homo Sapiens Agenda (2015) about the email correspondence between Simon and another male student from his high school. Digital correspondence and Simon's voiceovers form the backbone of the storytelling. Comparing the book and the film, with a particular focus on the written form of communication and the narrator's inner voice, one can observe differences between the textual and visual forms, especially when considering the narrative line. This paper examines how the novel as a text centered on digital correspondence is transformed in the film adaptation. The paper aims to reveal how the role of the narrator changes from novel to film in the context of Plato's mimesis and diegesis. The similarities and differences between the use of text through the narrative line are analyzed within the scope of adaptation theory and poststructuralist textual analysis, and the transformation of mimetic and diegetic epistolary storytelling into diegetic and non-diegetic speeches, sounds and visuals in the film universe. As a result, it has been revealed that the film has mega-textual features in the context of adaptation and correspondence, that it has been adapted to the film without losing the characteristics of the story through intertextuality, that it stands at a point of transmission, that it successfully visualizes the anonymity in correspondence, and that it carries the plot and the identity of the characters to the visual dimension.